Taqsīm as a Creative Musical Process in Arabic Music - Alkaei, Zaher; Küssner, Mats B. (Frontiers in Psychology, 2021)
Creativity plays a major role in various musical contexts including composition, performance and education. Although numerous studies have revealed how creativity is involved in processes of listening, improvising and composing, relatively little is known about the particularities of transcultural creative processes in music. In this article, we aim to shed light on the creative musical processes underlying taqsīm performance in Arabic music. To that end, qualitative interviews have been conducted with three Berlin-based oud players from Syria. Results of a thematic content analysis show that taqsīm encompasses multiple components (e.g., a flexible form and dependency on maqam as well as tonal music) and serves various functions such as developing artistic individuality. Moreover, taqsīm is affected by interactions between tradition and novelty. We discuss the interview data within the cross-cultural experiential model of musical creativity developed by Hill (2018), offering a fresh approach to studying taqsīm which goes beyond established concepts such as the improvisation-composition continuum.